The Influence of Thidiazuron on Direct Somatic Embryo Formation from Various Types of Explant in Phalaenopsis amabilis (L.) Blume Orchid - Windi Mose; Ari Indrianto; Aziz Purwantoro; Endang Semiarti (Bogor Agricultural University, Indonesia, 2017)
Phalaenopsis amabilis is an important national flower of Indonesia as a parent for orchidbreeding, so that needs a good strategy to produce high number of plants. The objective of this research is to analyze the use of thidiazuron (TDZ) for producing high number of plantlets, through directly induction of somatic embryos (SEs) from various explants. The method was used 20 each of protocorms, leaves, stems and roots as explants. The explants were dissected transversely, then put on various culture media: New Phalaenopsis (NP) and NP + (1, 2, 3) mgL−1 TDZ. Cultures were maintained at 25°C with continous white light. The formation of SEs was observed every week for 8 weeks. The results showed that SEs formation increased inline with the addition of TDZ concentration to the NP medium, for both velocity and amount of SEs formation. In NP0, SEs were formed at (26.07 ± 0.73) days after inoculation of protocorm, whereas on NP + (1, 2, and 3 mgL−1) TDZ, SEs were formed at (17.85 ± 0.67) days, (15 ± 0.64) days, and (11 ± 0.64) days, respectively. All types of explants formed SEs on NP + TDZ (1–3 mgL−1), whereas only 14 of 20 protocorms produced SEs (70%), and 8 of 20 stems formed SEs (40%) in NP0. In roots, SEs was formed on NP + 2 mgL−1 TDZ and NP + 3 mgL−1 TDZ. For stems, the highest amount of SEs (28.25 ± 1.07) was reached on NP + 3 mgL−1 TDZ, followed by protocorm (23.30 ± 1.13) SEs and roots (8.25 ± 0.68) SEs. In contrast, in NP0, the amount of SEs was very low (1.25 ± 0.46) from stem and (1.50 ± 0.65) from protocorms, there was no evidence of SEs formation in the leaves and roots.